Using some cooperative learning structures to increase efl learners' motivation in speaking and improve their speaking performance: a case study of grade 10 students at Mang Thit high school, Vinh Long province - Nguyễn, Thị Minh Trinh (Trường Đại học Cần Thơ, 2008)
In this paper, i report the results of my study on the effectiveness of using cooperative learning structures in speaking classes. The study aims to find out (1) the effectiveness of using cooperative learning structures to increase learners' motivation in speaking and improve their speaking performance (2) the correlation between motivation in learning to speak and speaking performance, and (3) learners' attitudes towards,...